(untitled) (Applied Biological Research, 2019)
Pesticides are extensively used across the globe to combat pests for higher crop production (Kohler and Triebskorn, 2013). In modern farming the use of intensive agriculture practices is mostly criticized as it adversely affects the environmental health, contaminate soil and reduces biodiversity (Datta et al., 2016). More than 99.7% pesticides used in agriculture are persistent and accumulate in surrounding environment (Tejada et al., 2017). Pesticides adversely affect soil organisms including earthworm (Maboeta et al., 2004). Earthworms, the major biomass of soil macrofauna, are highly susceptible to chemicals so are considered as pollution-indicator soil organism (Jouquet et al., 2010). The ingestion of soil minerals and organic material by earthworm facilitates humification and mineralization of soil nutrients. The pesticide residues in soil cease the physiological function and ecological structure of earthworms and cause their mortality (Maboeta et al., 2004) as well as damage higher trophic levels (Van Gestel et al., 2011). Since earthworm is a significant route for the uptake of soil contaminants, therefore toxicity study on earthworms may help in understanding the mechanism by which these pesticides affect the soil quality, especially soil biota. Emamectin benzoate is a semisynthetic bioinsecticide composed of naturally occurring compound, avermectin, extracted from Streptomyces avermitilis. Emamectin benzoate is used to control lepidopteron insects in vegetables, cotton and tobacco. Emamectin benzoate is a chloride channel activator that prevents muscle contraction, induces cessation of feeding and finally causes the death of pests. Earlier the toxic effects of antibiotics on earthworm have been demonstrated in many studies (Gunn and Sadd, 1994; Diao et al., 2007). However, the chemical used in present study has been studied for the first time under Kumaun (Uttarakhand) agroclimatic conditions.